PEMIKIRAN IBNU KHALDUN DALAM ILMU ADMINISTRASI NEGARA - Wisber Wiryanto (Al-Idarah: Jurnal Manajemen dan Administrasi Islam, 2020)
Ibn Khaldun (1332-1406) was a classical Muslim scholar and the author of Mukaddimah books which contains both naqli and aqli branches of science, include political science. Then, in the Western, there is a dichotomy paradigm of political-public administration (1900-1926) and public administration as administration science (1956-1970), and this science were developed until now. It was shown, there is relevance both political and public administration. So it can be assumed, the Mukaddimah book also contains a concept that has relevance with public administration science. Therefore, a study was conducted with a problem formulation, how did Ibn Khaldun's thoughts on public administration science? The research objective was to identify the concepts of Ibn Khaldun's thoughts on public administration science and its categories on the micro aspect. This research uses library research with focusing on public administration science as a research object, and Mukaddimah books as a data source namely research subject. The results are shown, Ibn Khaldun's concept of thought on the micro aspects, namely personnel, organization and government management in his time which has relevance to contemporary public administration science. Stakeholders need to apply public administration sourced from the al-Qur'an and Hadith as well as Islamic legacy, and proposes to reward Ibn Khaldun as the founding father of public administration.